2001
DOI: 10.1046/j.1365-2249.2001.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial analysis of serum and ascitic fluid levels of soluble adhesion molecules and chemokines in patients with spontaneous bacterial peritonitis

Abstract: SUMMARYThe aim of this work was the evaluation of serum and ascitic fluid levels of chemokines (IL-8, growthregulated oncogene (Gro-a ), and monocyte chemotactic protein-1 (MCP-1)), and of soluble adhesion molecules (P-selectin, E-selectin, l-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1)) in patients with spontaneous bacterial peritonitis (SBP). These compounds were serially analysed in serum and ascitic fluid by ELISA in patients with SBP (n 20), non-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…This study aimed at evaluating the role of serum calprotectin as a non-invasive diagnostic marker for SBP in Egyptian cirrhotic patients in comparison to CRP. Regarding the ascitic fluid cell count in the current study, there were higher levels of ascitic TLC and PMNL count in SBP group in comparison to the group with sterile cirrhotic ascites, and this result is in agreement with Girón-González et al (16) , Yildirim et al (17) and Abdel-Razik et al (18) . As regards ascitic fluid total protein, it was significantly higher in SBP group than in sterile cirrhotic ascites group (P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…This study aimed at evaluating the role of serum calprotectin as a non-invasive diagnostic marker for SBP in Egyptian cirrhotic patients in comparison to CRP. Regarding the ascitic fluid cell count in the current study, there were higher levels of ascitic TLC and PMNL count in SBP group in comparison to the group with sterile cirrhotic ascites, and this result is in agreement with Girón-González et al (16) , Yildirim et al (17) and Abdel-Razik et al (18) . As regards ascitic fluid total protein, it was significantly higher in SBP group than in sterile cirrhotic ascites group (P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…[6][7][8][9][10][11] Experiments were performed using an in situ perfusion system of the rat femoral bone marrow. Thus, the chemokine rat MIP-2 was infused directly into the femoral bone marrow via the femoral artery, and mobilized leukocytes were collected via cannulation of the femoral vein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that plasma levels of CXC chemokines rise during inflammatory reactions and contribute to the acute release of neutrophils from the bone marrow. [6][7][8][9][10][11] Therefore, to mimic an inflammatory reaction we have infused a pulse of the CXC chemokine, rat macrophage inflammatory protein-2 (MIP-2) to stimulate an acute mobilization of neutrophils from the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported increased sICAM-1 and sVCAM-1 values in patients with inflammatory diseases of the liver (34)(35)(36)(37)(38). While, elevated serum VCAM-1 in chronic hepatitis have been reported by some authors (39,40).…”
Section: Discussionmentioning
confidence: 87%